Nursing support for older people's autonomy in residential care: An integrative review - Moilanen Tanja; Suhonen Riitta; Kangasniemi Mari (WILEY, 2022)
Background
Nurses play a crucial role in enabling older people's autonomy in residential care. However, there is a lack of synthesised knowledge about how nurses can support older people.
Objective
The aim of this study was to identify and synthesise nursing support for older people's autonomy in residential care.
Methods
An integrative review was carried out by searching the CINAHL, Philosopher's index, PubMed, SocINDEX, Scopus and Web of Science databases, supplemented by manual searches. The searches focused on peer-reviewed scientific empirical research papers published in English, without date limitations. The constant comparison method was used for the analysis.
Results
The review identified 24 papers, and these showed that older people's autonomy was based on dignity. Nurses protected older people's autonomy in eight different ways. They protected their right to make their own decisions, acted as advocates, respected their wishes, provided opportunities for autonomy, fostered independence, gave information to residents and relatives, provided individualised care practices and protected older people's safety. However, there were also barriers that needed to be overcome.
Conclusions
Nurses used multiple, individually tailored activities to support older people's autonomy, but they also had different reasons for supporting or hindering it. Work and leadership structures are needed to ensure that older people's autonomy is driven by ethical practices.
Implications for practice
The results of this review can help nurses who provide residential care for older people to recognise the different nursing activities that can be used to support older people's autonomy and to develop strategies to apply them in different daily care situations. However, further research is needed to determine how these activities can be realised in daily care and how they cover different aspects of older people's lives in residential care.